Gc-protein-derived macrophage activating factor counteracts the neuronal damage induced by oxaliplatin. Issue 2 (February 2015) - Morucci, Gabriele; Branca, Jacopo J.V.; Gulisano, Massimo; Ruggiero, Marco; Paternostro, Ferdinando; Pacini, Alessandra; Di Cesare Mannelli, Lorenzo; Pacini, Stefania
Abstract : Oxaliplatin-based regimens are effective in metastasized advanced cancers. However, a major limitation to their widespread use is represented by neurotoxicity that leads to peripheral neuropathy. In this study we evaluated the roles of a proven immunotherapeutic agent [Gc-protein-derived macrophage activating factor (GcMAF)] in preventing or decreasing oxaliplatin-induced neuronal damage and in modulating microglia activation following oxaliplatin-induced damage. The effects of oxaliplatin and of a commercially available formula of GcMAF [oleic acid-GcMAF (OA-GcMAF)] were studied in human neurons (SH-SY5Y cells) and in human microglial cells (C13NJ). Cell density, morphology and viability, as well as production of cAMP and expression of vascular endothelial growth factor (VEGF), markers of neuron regeneration [neuromodulin or growth associated protein-43 (Gap-43)] and markers of microglia activation [ionized calcium binding adaptor molecule 1 (Iba1) and B7-2], were determined. OA-GcMAF reverted the damage inflicted by oxaliplatin on human neurons and preserved their viability. The neuroprotective effect was accompanied by increased intracellular cAMP production, as well as by increased expression of VEGF and neuromodulin. OA-GcMAF did not revert the effects of oxaliplatin on microglial cell viability. However, it increased microglial activation following oxaliplatin-induced damage, resulting in an increased expression of the markers Iba1 and B7-2 without any concomitant increase in cell number. When neurons and microglial cells were co-cultured, the presence of OA-GcMAF significantly counteracted the toxic effects of oxaliplatin. Our results demonstrate that OA-GcMAF, already used in the immunotherapy of advanced cancers, may significantly contribute to neutralizing the neurotoxicity induced by oxaliplatin, at the same time possibly concurring to an integrated anticancer effect. The association between these two powerful anticancer molecules would probably produce the dual effect of reduction of oxaliplatin-induced neurotoxicity, together with possible synergism in the overall anticancer effect.